Role of business age, scale & risk in debt financing choices for the Pakistani textile & apparel industry - Zahid Bashir; Muhammad Usman Arshad; Muhammad Asif; Muhammad Abbas; Hasnain Ali (Financial Internet Quarterly, 2020)
The motivation for this research enquiry is to identify the role of the business age, size and risk for the choice of debt financing in the textile and apparel sector of Pakistan along with other controlled factors. The textile and apparel sector of Pakistan comprises 464 listed entities as the targeted population while the study randomly finalized 60 firms as the sample after carefully analyzing the required information from the financial statements during the annual revenue streams of 2013-2019. The predicted variable for this research enquiry is measured by short, long and total-debt ratios while the predictor variables include the business age, firm's scale and risk. In addition, the research includes tax shield, tangibility, liquidity, profitability, and growth as the controlling factors. The study estimated that the choice of total-debt ratio is strongly affected by business age, size and risk along-with tax shield, tangibility, liquidity and profitability while the choice of short-term debt ratio mainly depends upon the firm's scale and age along with the tax shield. In addition, the choice of long-term debt ratio is strongly explained by the firm's scale and age along with the tax shield, liquidity and profitability.
Keywords: B23; B26; B41; C23; C58; G11; G32; 330; Debt Financing Choice; Business age; Firm's scale; Risk; Textile industry; Pakistan